Caracterización de la productividad de una empresa mexicana desarrolladora de tecnología mediante control difuso; Characterization of the productivity of a Mexican technology development company through fuzzy control - Agustín I. Cabrera Llanos; Francisco Ortiz Arango; Griselda Dávila Aragón (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The development of a model that allows measuring the productivity of a technology-based company is presented, which is based on the interactions identified between the investment of the research department, computer fraud, and theft. These interactions are presented through a model of fuzzy variables in which the membership functions are developed for each of these. Likewise, the interaction rules are developed based on the conjunction of the fuzzy sets proposed for the Mamdani model. With these designs, it is possible to determine the degree of productivity, characterized by a fuzzy set. To test the model, Monte Carlo simulation was used with four scenarios. The simulations' series results show that the fuzzy sets described allow to measure company's productivity being analysed through the proposed fuzzy sets productivity ranges.
Keywords: C63; C67; O32; 330; productivity; technology-based company; fuzzy logic; Monte Carlosimulation